Genome-wide identification of the KNOTTED HOMEOBOX gene family and their involvement in stalk development in flowering Chinese cabbage - Ou, Xi; Wang, Yudan; Li, Jingyi; Zhang, Jiewen; Xie, Zhenbin; He, Bing; Jiang, Zhehao; Wang, Yuting; Su, Wei; Song, Shiwei; Hao, Yanwei; Chen, Riyuan (Frontiers in Plant Science, 2022)
Gibberellin and cytokinin synergistically regulate the stalk development in flowering Chinese cabbage. KNOX proteins were reported to function as important regulators of the shoot apex to promote meristem activity by synchronously inducing CTK and suppressing GA biosynthesis, while their regulatory mechanism in the bolting and flowering is unknown. In this study, 9 BcKNOX genes were identified and mapped unevenly on 6 out of 10 flowering Chinese cabbage chromosomes. The BcKNOXs were divided into three subfamilies on the basis of sequences and gene structure. The proteins contain four conserved domains except for BcKNATM. Three BcKNOX TFs (BcKNOX1, BcKNOX3, and BcKNOX5) displayed high transcription levels on tested tissues at various stages. The major part of BcKNOX genes showed preferential expression patterns in response to low-temperature, zeatin (ZT), and GA3 treatment, indicating that they were involved in bud differentiation and bolting. BcKNOX1 and BcKNOX5 showed high correlation level with gibberellins synthetase, and CTK metabolic genes. BcKONX1 also showed high correlation coefficients within BcRGA1 and BcRGL1 which are negative regulators of GA signaling. In addition, BcKNOX1 interacted with BcRGA1 and BcRGL1, as confirmed by yeast two-hybrid (Y2H) and biomolecular fluorescence complementation assay (BiFC). This analysis has provided useful foundation for the future functional roles’ analysis of flowering Chinese cabbage KNOX genes